Three Paths Of/To Communism - Škabraha, Martin (Dějiny – teorie – kritika, 2010)
The aim of this study is to offer a more comprehensive view of communism than is usual in the Czech public arena these days, by means of an exposition of the concept of criticism, using the example of communism itself conceived as radicalized modernity. Three forms of critique are distinguished: 1) Conversion, which refers to the values in the official canon, attempting to interpret them in favour of the unprivileged; communism in this sense thinks through the promises of capitalism. 2) Subversion in the spirit of the „hermeneutics of suspicion“, which seeks the „real“ hidden motive (e.g. instinct, the will to power, class struggle) behind predominant ideas, realizing revolutionary intervention on this basis. 3) Controversy in the spirit of „reflexive modernization“, referring to the unintended consequences of modernity and politicizing private activity. Communism is presented as an example of these forms of criticism, and at the same time the latter are used to interpret its „meaning of history“.